The experiences of healthcare workers on the delivery of healthcare service during Covid-19 Pandemic in clinics Sub-district A, City of Johannesburg Municipality Gauteng Province - Ncube, Senzeni Joy (My University, 2023)
Background: The novel coronavirus (COVID-19) epidemic has invaded health systems throughout the world. The study findings present many difficulties for healthcare practitioners. This study summarizes the studies that came out during the first year of the pandemic. Purpose: To determine the experience of the healthcare workers on the delivery of healthcare service during the COVID-19 pandemic in clinics sub-district A, city of Johannesburg municipality Gauteng province. Study method: A qualitative, phenomenological, descriptive, and contextual design was applied to explore and describe the experiences of healthcare workers on the delivery of healthcare services during the COVID-19 pandemic in clinics sub-district A, city of Johannesburg municipality Gauteng province. A purposive and convenient, the non-probability sampling method was used to select 24 healthcare workers, two doctors and 22 nurses. Data collection was completed with an unstructured interview that lasted between 25 and 40 minutes. Data were analyzed using Techs’ open coding method of qualitative data analysis. Results: The following themes emerged: Diverse experiences of the healthcare workers when delivering service during the COVID-19 pandemic, diverse experience regarding support systems when providing health services during the COVID-19 pandemic, challenges regarding the provision of care during the COVID-19 pandemic and suggestions on how to improve the service provision during COVID-19 pandemic. Conclusion: The COVID-19 pandemic has put a significant strain on healthcare systems around the world, including South Africa. COVID-19 pandemic demanded healthcare workers to be resilience when providing service delivery, according to interviews with healthcare workers in Johannesburg. The study's results will be presented to the Gauteng health department and nurses. The study has examined the necessary intervention and support of healthcare workers to improve patient care. It will also provide policymakers with robust data to inform urgent decision-making regarding 8 workforce protection, support, and sustainability.
Thesis (M. A. (Nursing)) -- University of Limpopo, 2023
Keywords: COVID-19; Healthcare workers; Health services accessibility; Medical care -- South Africa -- Gauteng; Medical personnel; COVID-19 Pandemic, 2020-; Disease management